Comparison of frameworks for defining land occupation considering on-farm and off-farm feed production on Italian dairy farms - Gabriele Rolando; Francesco Ferrero; Stefania Pasinato; Luciano Comino; Daniele Giaccone; Ernesto Tabacco; Giorgio Borreani (Journal of Dairy Science)
ABSTRACT: Land occupation (LO) is one of the most frequently discussed aspects of livestock competition with agricultural activities. In this study, the area needed to produce purchased feeds for animal nutrition was used to estimate the off-farm land occupation of dairy farms, allowing for a precise calculation of the total land occupation requirement for milk production (on-farm plus off-farm LO, expressed in m2 per unit of standardized milk). We use 4 approaches (designated LO1, LO2, LO3A, and LO3B) to calculate the off-farm land used for milk production on dairy farms, and applied them to 14 dairy farms in northern Italy as a case study. The LO1 used mass allocation of each purchased product between the fraction of DM yield of each product (main, byproducts, and crop residues) derived from the whole crop. This procedure was considered as the reference. The LO2 considered only the main product as the driver of land use, without considering byproducts. The LO3A and LO3B approaches converted all the purchased feeds into energy, protein, and fiber equivalents. The LO1 was accurate, even though it was time-consuming, whereas the procedures of LO3A and LO3B showed comparable values with easier required input data. When total LO was considered (on-farm and off-farm using LO1), the average surface to produce milk resulted in 1.47 m2/kg of fat- and protein-corrected milk (FPCM); however, the off-farm LO1 was 0.76 m2/kg FPCM (± 0.24 m2/kg). This large variability indicates that LO largely depends on farm management and adopted animal feeding strategies. Moreover, half of the milk production was linked to the purchased feeds. We found positive correlations between all off-farm LO approaches and N surplus (r = 0.45 to r = 0.73), supporting previous studies suggesting that concentrated animal agriculture, in which the fulfillment of the animal's needs has been delegated to purchased feeds, is the main source of nitrogen surplus on farmlands. The LO per unit of production can be reduced by increasing on-farm feed production, particularly protein components, and to a lesser extent by valorizing byproducts, while not increasing the on-farm N surplus and carbon footprint.